Estimated Profits of Rengginang Lorjuk Madura by Used Comparison of Holt-Winter and Moving Average - Erwin Prasetyowati; Imron Rosyadi NR; Matsaini Matsaini (IAES Indonesia Section, 2020)
Rengginang Lorjuk is a typical Madura food that is ordered more by SMEs and is found in Sumenep Regency and several other areas in Madura. This product is made for supplies and orders, where demand will surge at certain times. Therefore, SMEs of Rengginang Lorjuk is required to have good planning in determining the selling price in accordance with the revenue target obtained. Considering that the main raw materials used are sticky rice and ensis leei (lorjuk) are raw materials that have fluctuating prices, this studio compares forecasting methods namely Holt Winter (HW) and Moving Average (MA), supported by MSE and MAPE, in order to obtain accurate forecasting results. These forecasting results show that HW has better accuracy than the MA, which is then used to calculate the cost of production with an Activity-Based Costing system, which requires charging costs for all activities carried out in production, namely the cost of raw materials, direct labor costs, and overhead factory fee. Using MAPE values, this study yields 4 estimates of production costs in accordance with changes in raw material costs.